John Fiske's Semiotic Analysis in The Spotlight Film - Meutia Sabarini (Universitas Ahmad Dahlan, 2021)
Freedom of the press has become one of the most discussed topics being questioned in the practical, whether it exists. Another issue the press has been facing is that the images of journalists shown in the films are bad. A meta-analysis study concluded a relationship between the image of reality from the film and people’s behavior in responding to it. Journalists in a film are generally shown as rude characters. Therefore, to better explain the topic of journalism contained in a film, this article will discuss The Spotlight Film. The film pictured these issues that the press and its journalists usually face in serving the public with accurate and credible information. This study uses a qualitative descriptive design and John Fiske’s semiotic theory in analyzing that containing clear and detailed information related to data in the form of descriptions. The result of this study shows 1) In the reality level of John Fiske’s theory, The Spotlight showed that journalists base their coverage on accredited sources as their role as a mass media that functions to support social change with access to reliable news sources which are then conveyed to the broader community. 2) At the representation level, the State of Play further reinforces the image of the media and its power. It portrayed the press as heroic and helped legitimize its position as an institution. 3) At the ideology level, the film relies heavily on toxic news values, best described as journalists’ hunches. The Spotlight described an extensive investigative process that most newsrooms do not follow, as modern newsgathering occurs mainly in news agencies and press releases.